Effect of Leverage, Growth, Firm Size, Dividend Policy, and Interest Rate on Company Value - Yudha Pradana, Ivan (Dinasti International Journal of Economics, Finance & Accounting, 2021)
The purpose of this study is to determine influence of Leverage, Growth, Firm Size, Dividend Policy and Interest rate on the value of the company of construction and building sub-sector companies listed on the Indonesia Stock Exchange during the observation period 2014 - 2020. The research sample in this study consists of 7 companies determined by conducting purposive sampling. In this study, uses secondary data from financial statements were reported by construction and building sub-sector companies. Research methods uses descriptive statistics and inferential statistics using the Random Effect Model. The results showed that Leverage and Interest Rate have a significant positive effect, Firm Size has a negative and significant effect. While the Growth and Dividend Policy has no effect on the value of the company.